2014
DOI: 10.1002/ijc.29206
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Epstein–Barr virus microRNAs miR‐BART7 and miR‐BART13 as biomarkers for nasopharyngeal carcinoma diagnosis and treatment

Abstract: More than 75% of nasopharyngeal carcinoma (NPC) patients have already developed local or regional spread at diagnosis, which hampers effective treatment and results in a poor prognosis. It is essential to characterize more sensitive and specific biomarkers for screening of high risk individuals and assessment of NPC treatment effectiveness. NPC is an Epstein-Barr virus (EBV) associated tumor in which only a few viral proteins but more than 20 BamHI A rightward transcripts (BART) microRNAs are detected, at abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 48 publications
6
95
0
Order By: Relevance
“…Circulating miRNAs of EBV have been proposed to serve as diagnostic markers in patients with nasopharyngeal carcinoma, for example (34).…”
Section: Circulating Viral Mirnasmentioning
confidence: 99%
“…Circulating miRNAs of EBV have been proposed to serve as diagnostic markers in patients with nasopharyngeal carcinoma, for example (34).…”
Section: Circulating Viral Mirnasmentioning
confidence: 99%
“…For example, a previous study has demonstrated that miRNA testing is adequately sensitive and specific for NPC confirmation, with a diagnostic sensitivity and specificity of up to 96% (13). However, some research has reported that miRNA testing achieved an efficacy <60% (10,14,15). Therefore, the present study conducted a comprehensive meta-analysis and aimed to assess the overall diagnostic performance of miRNA as biomarkers for NPC identification.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous studies have documented that deregulated miRNA expression is strongly linked to the occurrence of various carcinomas (7,8). It has become increasingly apparent that miRNA are of crucial importance for the carcinogenesis and progression of NPC, and therefore they have been highlighted as powerful screening predictors in confirming or monitoring NPC (9)(10)(11)(12)(13)(14)(15). Unfortunately, the clinical utility of miRNA signatures remain unpopular in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other pathogenic factors that are enriched in EBV exosomes such as EBV DNAs, EBV mRNAs and EBV miRNAs have also been shown to be potential biomarkers for EBV cancer diagnosis [56][57][58][59] ( Table 2). Using quantitative PCR (qPCR), Yip and colleagues showed that high-EBV DNAs could be detected in plasma/serum of NPC patients at late stages of disease and the viral loads were associated with poor survival or frequent relapse in NPC patients [56,59].…”
Section: Exosomes As Biomarkersmentioning
confidence: 99%
“…On the other hand, Zhang and co-workers showed that EBV miRNAs (miR-BART7 and miR-BART13) can serve as important biomarkers for NPC diagnosis and prediction of treatment efficacy [58]. The potential prognostic value of EGFR and HIF1α has been previously demonstrated in breast and prostate cancers [60,61].…”
Section: Novel Implications Of Exosomes In Diagnosis and Treatment Ofmentioning
confidence: 99%